Origin and evolutionary history of Populus (Salicaceae): Further insights based on time divergence and biogeographic analysis - Liu, Xia; Wang, Zhaoshan; Wang, Wei; Huang, Qinqin; Zeng, Yanfei; Jin, Yu; Li, Honglei; Du, Shuhui; Zhang, Jianguo (Frontiers in Plant Science, 2022)
Populus (Salicaceae) species harbour rich biodiversity and are widely distributed throughout the Northern Hemisphere. However, the origin and biogeography of Populus remain poorly understood. In this study, we infer the divergence times and the historical biogeography of the genus Populus through phylogenetic analysis of 34 chloroplast fragments based on a large sample. Results show that Eurasia is the likely location of the early divergences of Salicaceae after the Cretaceous-Paleogene (K-Pg) mass extinction, followed by recurrent spread to the remainder of the Old World and the New World beginning in the Eocene; the extant Populus species began to diversity during the early Oligocene (approximately 27.24 Ma), climate changes during the Oligocene may have facilitated the diversification of modern poplar species; three separate lineages of Populus from Eurasia colonized North America in the Cenozoic via the Bering Land Bridges (BLB); We hypothesize that the present-day disjunctions in Populus can be explained by two scenarios: (i) Populus likely originated in Eurasia and subsequently colonized other regions, including North America; and (ii) the fact that the ancestor of the genus Populus that was once widely distributed in the Northern Hemisphere and eventually wiped out due to the higher extinction rates in North America, similar to the African Rand flora. We hypothesize that disparities in extinction across the evolutionary history of Populus in different regions shape the modern biogeography of Populus. Further studies with dense sampling and more evidence are required to test these hypotheses. Our research underscores the significance of combining phylogenetic analyses with biogeographic interpretations to enhance our knowledge of the origin, divergence, and distribution of biodiversity in temperate plant floras.